Cocoa Farmers’ Adaptation to Climate Extremes in Atwima Nwabiagya North District, Ghana - Tham-Agyekum, Enoch Kwame; Boansi, David; Ankuyi, Fred; Edeafour, Patrick Padlass; Okorley, Ernest Laryea; Jones, Ebenezer Osei; Prah, Stephen; Rakotomarolahy, Patrick; Sharma, Rakesh; Bakang, John-Eudes Andivi (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
This study examines the adaptation strategies of cocoa farmers to climate extremes. The study multistage sampling technique to sample 400 farmers from 10 communities. Primary data was gathered with the use of structured questionnaire and the data was analyzed using descriptive and inferential statistics. A significant proportion of respondents have experienced extreme climate events, with drought (73%), flooding (64.25%) and heatwaves (56.75%) being the most commonly reported experiences. The most commonly used adaptation strategies reported are mixed cropping (73.50%), planting improved crop variety (68.75%), and cover cropping (70%). Adopting mixed cropping was influenced by education and access to extension. The drivers of adopting improved plant/seed variety were farm size, number of farms owned by a farmer, access to extension, access to credit and membership in a farmer cooperative. Distance to farm, education extension access and membership in farmer cooperative influences the adoption of cover crops as means to mitigate extreme climate. In the event of flooding, farmers are likely to adapt all the three main adaptation strategies. The promotion of farmer cooperatives should be a top priority for the stakeholders in the cocoa value chain. Top priority should be also given to the breeding of crop varieties that are resistant to extreme climatic conditions.